PENGARUH EDUKASI KESEHATAN TERHADAP PENGETAHUAN TENTANG GASTRITIS DI WILAYAH KERJA PUSKESMAS GELUMBANG TAHUN 2021 - Tiara Intan Fandini; R.A. Fadila (Jurnal Kesehatan dan Pembangunan, 2022)
Abstract Gastritis is a disease that tends to relapse, causing patients to have to seek treatment repeatedly. One of the factors that cause gastritis is the lack of public knowledge about gastritis. So to overcome gastritis in the community, an effort is needed to increase public knowledge, namely by providing education about gastritis. The purpose of this study was to determine the effect of health education on the level of knowledge of respondents about gastritis in the working area of ​​the Gelumbang Health Center. The research method used is quantitative research using pre-experimental research plan One group protest-posttest. The population in this study were patients with gastritis at the Gelumbang Health Center with a sample of 30 respondents. The results of the study obtained an average of patient knowledge before given health education about gastritis is 5.40 and the average knowledge of patients after being given health education has increased to 7.97. The results of the statistical test showed that there was an effect of health education on knowledge about gastritis in the Gelumbang Health Center Work Area in 2021 with a p value of 0.000. Suggestions are expected to the public in order to increase knowledge about gastritia disease which can be obtained from various sources such as books, electronic media (television), mass media (newspapers and magazines) and the internet so that their knowledge can take steps to prevent gastritis both for themselves as well as to all family members. Keywords: Health Education, Knowledge, Gastritis